SIMP Canosa: Integrated System for Monitoring and Prevention of environmental crime Video surveillance and satellite imagery for the territory monitoring (GEOmedia, 2015)
A Decision Support System improving the capacity of the Municipality forces toprevent and fight crimes such as traffic of dangerous waste, illegal landfills, illegalbuildings or archaeological and natural heritage damages.